Inspector of the Dead : Thomas De Quincey #2 - Morrell, David, 1943- (New York : Mulholland Books/Little, Brown, and Company, 2015)
"Thomas De Quincey, infamous for his Confessions of an Opium-Eater, confronts London's harrowing streets to thwart the assassination of Queen Victoria. The year is 1855. The Crimean War is raging. The incompetence of British commanders causes the fall of the English government. The Empire teeters. Amid this crisis comes opium-eater Thomas De Quincey, one of the most notorious and brilliant personalities of Victorian England. Along with his irrepressible daughter, Emily, and their Scotland Yard companions, Ryan and Becker, De Quincey finds himself confronted by an adversary who threatens the heart of the nation. This killer targets members of the upper echelons of British society, leaving with each corpse the name of someone who previously attempted to kill Queen Victoria. The evidence indicates that the ultimate victim will be Victoria herself. As De Quincey and Emily race to protect the queen, they uncover long-buried secrets and the heartbreaking past of a man whose lust for revenge has destroyed his soul. Brilliantly merging historical fact with fiction, Inspector of the Dead is based on actual attempts to assassinate Queen Victoria"--.
Keywords: De Quincey, Thomas, -- 1785-1859 -- Fiction; Fathers and daughters -- Fiction; Serial murderers -- Fiction; Murder -- Investigation -- Fiction; FICTION / Romance / Gothic; FICTION / Mystery & Detective / Historical; FICTION / Suspense; London (England) -- Social life and customs -- 19th century -- Fiction; Biographical fiction; Historical fiction; Mystery fiction